(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The transformations that are taking place in recent years in the hands of the growing technological advances suggest the need to reflect on the changing forms of work, which is why we emerge from the late twentieth century new ways of working which common link is carrying out the work from their own homes, outside the scope of the office through the use of information technology and communication (ICT), this new way of working is called telecommuting.